Perencanaan Strategi Sistem dan Teknologi Informasi pada Perusahaan Telepon Genggam PT. Sinar Jaya Sukses Mandiri - Kartawiguna, Daniel; Hidayat, Junifar; Anjani, Riskha Julia; Hasionellis, Aris J. (Bina Nusantara University, 2011)
PT. Sinar Jaya Sukses Mandiri (PT. SJSM) is a company engaged in telecommunications. In carrying out its business activities, PT. SJSM has not maximized the utilized the information system (IS) and information technology (IT). This research aims to produce strategic information systems planning and technology at PT. SJSM that will support the business strategy. The research uses is the data collection method by doing bibliography study, observation and interviews, and analysis and planning method by conducting an analysis of internal and external environment of business and company IS/IT using value chain analysis, SWOT, CSF, Porter?s five forces, and PEST. This research produces a recommendation of strategic planning and information technology systems of PT. SJSM including IS/IT management strategy, IS business strategy and IT strategy. The conclusions of this research is that information system and information technology strategies are needed to support the achievement of the vision, mission and corporate objectives, and are expected to increase the company competitiveness.